Peningkatan Kesadaran Bencana Sejak Dini Melalui Sosialisasi Mitigasi Bencana Di Wilayah Kodim 0205/Tanah Karo - Daniel Ginting; Farida Ariani Pelawi; Nina Fentiana (Lembaga Pengembangan Kinerja Dosen, 2025)
Children are one of the most vulnerable groups during disasters due to their limited physical and psychological resilience. Therefore, providing disaster mitigation education to children is essential to enhance their awareness, preparedness, and response capabilities in the face of potential disasters. This community service activity aims to increase children's understanding of disaster mitigation through both theoretical education and participatory simulations that reflect real-life scenarios. The activities were carried out using a cooperative-participatory approach in collaboration with the local Indonesian Red Cross (PMI) in Tanah Karo and members of the surrounding community. The stages of implementation included conducting a site survey, securing necessary permits, determining the time and location, coordinating with local stakeholders, and executing the service program. The educational activities covered disaster phases, including pre-disaster, during disaster, and post-disaster, with a focus on practical and age-appropriate learning strategies. The educational team involved an interprofessional group of facilitators who delivered the material through socialization and counseling sessions. The sessions were enthusiastically received by the children, indicating a high level of engagement and interest. However, findings revealed that children's knowledge of disaster mitigation was still minimal, emergency response plans were underdeveloped, and community involvement in disaster preparedness training remained low. This highlights the need for continuous and sustainable disaster education efforts, especially for children and communities in disaster-prone areas. By fostering early awareness and preparedness through ongoing education and simulation-based activities, it is expected that children will be better equipped to respond effectively and safely during disaster situations. Long-term, this approach also aims to build a more resilient and disaster-aware community.